HIGHER EDUCATION TRENDS IN THE STUDIES OF THE EUROPEAN UNION - Mospan, Natalia V. (Educological discourse, 2014)
The article presents an analysis of pedagogical and sociological studies of European scientists that address the impact of globalization, mercerization and internationalization in the development of higher education in the European Union, namely the analysis and display of the effects of market relations in higher education. Here is determined the external and internal problems of higher education at the present stage. They include market relations in higher education, aimed at changing the nature and role of higher education institutions in society, inadequate reforms in higher education and the lack of an appropriate legislative framework, that create obstacles to the development of the European higher education area. Prospects for further study of the problem are in the light of trends of development of higher education in Ukraine in the conditions of modern social changes.